From Likes to Purchases: Analyzing the Impact of Instagram Marketing on Online Shoppers - Wicaksono, Trio Bayu (Journal of Business, Management, and Social Studies, 2023)
This study examines how social media users feel about influencers and sponsored material based on factors including credibility, entertaining postings, and informativeness. Then, consider how these factors relate to users’ intentions to buy in the context of Instagram marketing. This research paper collected data from 418 respondents through an online questionnaire. The questionnaire requires the respondents who are social media user, especially Instagram, millennials and Gen Z who is currently a university student who lived in Jakarta, and those who are following influencer on Instagram at least 3 influencers and who have purchased product and or services online. Statistical analyses are performed in this study. Findings – The result shows that the activity of influencers on Instagram has an impact on consumer behavior. Therefore, marketers in any kind of industries should consider the long-term impact that marketing influencer can give to their company. This study offers fresh perspectives on the efficacy of influencer marketing for millennials and Generation Z on Instagram in Jakarta, Indonesia. It highlights the need of carefully choosing influencers according to their unique approaches and comprehending the requirements of the target market, providing helpful advice to digital marketers hoping to increase the influence of influencer activities on consumer behavior and purchase decisions.